1998
DOI: 10.1002/(sici)1096-8652(199802)57:2<176::aid-ajh14>3.3.co;2-w
|View full text |Cite
|
Sign up to set email alerts
|

Deep‐vein thrombosis and coumarin skin necrosis associated with a factor V inhibitor with lupus‐like features

Abstract: We report a 71-year-old man who developed deep-vein thrombosis after major surgery. Coumarin skin necrosis developed after starting oral anticoagulant therapy. An inhibitor to factor V (61 Bethesda units) with lupus-like features was found as well as a low protein C level. The occurrence of these very rare findings indicates that despite profound procoagulant inhibition (factor V inhibition and anticoagulant therapy), hypercoagulation can occur. Am.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0
1

Year Published

2001
2001
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 10 publications
(11 reference statements)
0
20
0
1
Order By: Relevance
“…12 Only 3 cases of patients with antibodies to factor V have been associated with thrombotic events. However, 2 of the 3 cases had an autoimmune syndrome where lupuslike anticoagulant activity was demonstrated in association with anticardiolipin antibodies, 13,14 whereas the antifactor V antibody in the third case was associated with Sjögren syndrome. 15 It is interesting to note that in all 3 cases prolongation of the basal clotting time was present, suggesting an interference with the procoagulant function of factor V. It has been demonstrated in one case (Sjögren syndrome 15 ) that although the antibody in vitro did not inhibit activated protein C activity toward factor Va, it was able to inhibit the procoagulant function of factor V. It is well established that the binding to a membrane surface is necessary for both normal procoagulant expression of factor Va cofactor activity as well as efficient down-regulation of its activity by APC.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…12 Only 3 cases of patients with antibodies to factor V have been associated with thrombotic events. However, 2 of the 3 cases had an autoimmune syndrome where lupuslike anticoagulant activity was demonstrated in association with anticardiolipin antibodies, 13,14 whereas the antifactor V antibody in the third case was associated with Sjögren syndrome. 15 It is interesting to note that in all 3 cases prolongation of the basal clotting time was present, suggesting an interference with the procoagulant function of factor V. It has been demonstrated in one case (Sjögren syndrome 15 ) that although the antibody in vitro did not inhibit activated protein C activity toward factor Va, it was able to inhibit the procoagulant function of factor V. It is well established that the binding to a membrane surface is necessary for both normal procoagulant expression of factor Va cofactor activity as well as efficient down-regulation of its activity by APC.…”
Section: Discussionmentioning
confidence: 99%
“…Only 3 antifactor V antibodies have been demonstrated to cause thrombotic manifestations. However, these antibodies were not well characterized and, whereas 2 of them were associated with lupuslike symptoms, 13,14 the third antifactor V antibody was associated with Sjögren syndrome. 15 In the present manuscript, we present data from an individual with an antifactor V antibody that interferes with the anticoagulant pathway of blood coagulation.…”
Section: Introductionmentioning
confidence: 99%
“…However, the overlapping APC resistance results between controls and patients makes it difficult to apply this concept to individual patient care [41]. Patients have been reported to develop autoantibodies against factor V after exposure to bovine thrombin leading to APC resistance, with subsequent thrombosis of unclear etiology [42][43][44]. One study has also observed APC resistance (as measured by endogenous thrombin potential without dilution into factor V-deficient plasma) in unselected patients with untreated hematological malignancies, which may contribute to the increased risk of venous thrombosis observed in these patients [45].…”
Section: Apc Resistance Without Factor V Leidenmentioning
confidence: 99%
“…[2,3] For 3 patients, the AFVI appeared after the prescription of anti-vitamin K. A few case reports also described the onset of AFVI after treatment with anti-vitamin K, raising the question of its immutability. [5,6] Anti-vitamin K should thus be used with caution in the context of AFVI.…”
Section: Discussionmentioning
confidence: 99%
“…The remaining six patients were treated with heparin (LMWH or unfractionated heparin) during the initial phase followed by anti-vitamin K or oral anticoagulants. [6,[13][14][15] The treatment with heparin helped towards a favorable evolution of thrombosis.…”
Section: Discussionmentioning
confidence: 99%